Indonesian EFL Teachers’ Use of Code Mixing in Classroom Interactions - Zanna Nurpiana; Rahmah Fithriani (Journal of Vocational Education Studies, 2023)
Code Mixing (CM) is generally a communication strategy that is often used by teachers in the process of teaching English as a Foreign Language (EFL). This study aims to describe the types and categories of CM used by teachers in the context of teaching EFL in Indonesia, as well as investigate the perspectives of teachers and students regarding the use of code mixing in classroom interactions. This research uses case studies with a qualitative approach to analyze data. Data collection was carried out through recorded interviews with three teachers and seven students as well as observing the teaching and learning process during six meetings at one of the senior high schools in Medan, North Sumatera. The results of the study show the teachers use three types of CM, namely Insertion, Alternation and Congruent Lexicalization. There are 177 mixed code data found. There are 188 data classified as insertion type, 49 data classified as alternation type and 10 data classified as congruent lexicalization type. Then from the results of the interviews, the teacher considered that the functions of CM in students were 1) Improving student’ comprehension, 2) Encouraging students' independence in learning new vocabulary. Furthermore, students agreed that code mixing was an effective and effective learning strategy in increasing their understanding of English. This happened because 71.5% of students used English most often with some Indonesian language CM and 67.2% said the use of CM can help understand topic discussions in the learning process.